Ultrafast Sodiation of Single-Crystalline Sn Anodes - Choi, Yong-Seok; Byeon, Young-Woon; Park, Jun-Hyoung; Seo, Jong-Hyun; Ahn, Jae-Pyoung; Lee, Jae-Chul (American Chemical Society, 2018)
Sodiation was performed on crystalline Sn cylinders using an in situ electron microscope to evaluate the rate performance of the Sn anode by directly measuring the sodiation rate. We observed that the sodiation rate of the Sn anode is more than 2 orders of magnitude higher than the lithiation rate of the Si anode under the same conditions. This unprecedented rate displayed by the Na-Sn system is attributed to the bond characteristics and crystalline-to-amorphous transformation of the Sn crystal at the thin interface of the Na-Sn diffusion couple. Here, using atomic simulations, we explain how and why the Sn anode exhibits this high rate performance by resolving the diffusion process of Na ions in the Na-Sn interfacial region and the electron structure of the crystalline Sn. This work provides a useful insight into the use of Sn as an attractive anode material for realizing ultrafast-charging batteries for electric vehicles and mobile devices.
Keywords: LITHIUM-ION BATTERIES; HIGH-CAPACITY ANODE; ELECTROCHEMICAL LITHIATION; SILICON NANOWIRES; MOLECULAR-DYNAMICS; LI; DIFFUSION; SI; ELECTRODES; COMPOSITE